The responsibility of spouses for personal and common obligations - Kumysbekova, Zh.T. (KSU publ, 2015)
In the article, the author considers the personal and general obligations of the spouses of property character, determines the characteristics of the legal regime of jointly acquired property and personal property of the spouses, investigates the mechanism of execution of personal and general obligations of the spouses, reveals the sequence and priority of execution of obligations of spouses including the share of the joint property, and concludes imperfection of family law that provides the guarantees for the rights of creditors in relation to the marriage contract.
Keywords: spouses; obligations; marriage; property; the legal regime of marital property